1993
DOI: 10.1111/j.1600-0773.1993.tb01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Lithium on the Cyclic AMP Signalling System in Various Regions of the Brain ‐ Possible Relations to its Psychotropic Actions ‐: A Study on the Adenylate Cyclase in Rat Cerebral Cortex, Corpus Striatum and Hippocampus

Abstract: It has been estimated that in most industrialized countries 1 person out of every 1000 in the population is undergoing lithium treatment to stabilize their episodic mood disturbances due to manic-depressive illness. Lithium may stabilize mood swings by altering the action of certain neurotransmitters at the synaptic level in the brain. Recent research suggests that lithium alters neurotransmission by affecting neurotransmitter-coupled second messenger systems. A major second messenger system is the adenylate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 230 publications
0
12
0
Order By: Relevance
“…Another reason for delayed gene expression during lithium feeding to intact animals is the approximately 1-week half-life for lithium to reach a steady-state brain concentration, due to its slow penetration across the blood-brain barrier (Bosetti et al, 2002b). In this regard, lithium has been reported to target G-proteins (Li et al, 1993;Miki et al, 2001;Wang and Friedman, 1999), cyclic adenosine monophosphate (cAMP) (Mork, 1993;Mork and Geisler, 1995), protein kinase A (Mori et al, 1998), protein kinase C (PKC) (Manji et al, 1993(Manji et al, , 1996Soares et al, 2000) and its substrate MARCKS (Lenox et al, 1992;Watson and Lenox, 1996), glycogen synthase kinase-3 beta (GSK-3 b) (De Sarno et al, 2002), and activating protein 1 (AP-1) transcription factor (Ozaki and Chuang, 1997;Yuan et al, 1999). We reported that 6 weeks of lithium administration to rats, so as to produce therapeutically relevant plasma and brain lithium concentrations, resulted in reduced arachidonic acid (AA) turnover in brain phospholipids (Chang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Another reason for delayed gene expression during lithium feeding to intact animals is the approximately 1-week half-life for lithium to reach a steady-state brain concentration, due to its slow penetration across the blood-brain barrier (Bosetti et al, 2002b). In this regard, lithium has been reported to target G-proteins (Li et al, 1993;Miki et al, 2001;Wang and Friedman, 1999), cyclic adenosine monophosphate (cAMP) (Mork, 1993;Mork and Geisler, 1995), protein kinase A (Mori et al, 1998), protein kinase C (PKC) (Manji et al, 1993(Manji et al, , 1996Soares et al, 2000) and its substrate MARCKS (Lenox et al, 1992;Watson and Lenox, 1996), glycogen synthase kinase-3 beta (GSK-3 b) (De Sarno et al, 2002), and activating protein 1 (AP-1) transcription factor (Ozaki and Chuang, 1997;Yuan et al, 1999). We reported that 6 weeks of lithium administration to rats, so as to produce therapeutically relevant plasma and brain lithium concentrations, resulted in reduced arachidonic acid (AA) turnover in brain phospholipids (Chang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple studies suggesting its involvement in BP disorder, both because of alterations in its levels and activity [39][40][41][42] and because it is a target for lithium and other mood stabilizing agents. 43,44 In summary, we present evidence that, taken together with independent findings by other investigators, strongly suggests the presence of a gene for BP disorder on chromosome 8q24. Furthermore, we make an argument for more appropriate models in multipoint linkage of complex disorders that consider the likelihood of the existence of common variants with low penetrance in these diseases.…”
Section: Linkage Of Bipolar Disorder To 8q24 D Avramopoulos Et Almentioning
confidence: 74%
“…The adenylyl cyclase activity was measured as described by Mørk ( 23). In brief, whole pituitaries were homogenized in 50 vol.…”
Section: Methodsmentioning
confidence: 99%